Pemantauan Kemampuan Anak dalam Mencapai Tumbuh Kembang yang Optimal dengan Deteksi Tumbuh Kembang pada Anak Usia Prasekolah - Farida Yuliani; Erfiani Mail; Fitria Edni Wari (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2022)
This community service aims to monitor the growth and development of pre school children at PAUD Tarbiyatussibyan. The method used is a lecture and measuring growth and development. Monitoring and measurement of growth and development was carried out on 30 children in September-Nopember 2021. The results obtained were 100% of the participants had normal growth and development. Monitoring of growth and development should be done regularly at least once every 3 months as an effort to detect early developmental delays in pre-school children.